REVEALING SOCIAL RESTRICTIONS OF GENDER ROLES THROUGH CONVERSATIONAL ANALYSIS IN THE NOVEL MULAN BY ELIZABETH RUDNICK - Alfiyyah, Nurlita Farah (Faculty of Letters Universitas Balikpapan, 2026)
This research focuses on the social restriction of gender roles through conversation analysis in the novel Mulan. There are two objectives of the problem formulation, 1)To find out the forms of social restrictions in gender roles contained in the novel Mulan by Elizabeth Rudnick and 2)To find out how conversation analysis reveals social restrictions in gender roles in the novel Mulan by Elizabeth Rudnick. This study uses two theories, the first is John Stuart Mill's social theory, and the second is Grice's Conversation Analysis theory. The method used is qualitative research with primary data which the researcher presents in descriptive form. The results showed that the researcher found four social restrictions in gender roles, namely social restrictions of tolerance, diversity, democracy, justice and equitable society. Reveal the social restrictions in gender roles, the researcher used the Conversation Analysis theory which consists of four parts Maxim, namely Quality, Quantity, Manner, and Relevance. The researcher found that dominant social restriction in gender roles is justice and equitable society, which has an important influence on the community environment. In conclusion, social restrictions in gender roles, especially justice and equitable society can be revealed by using conversational analysis through conversational sentences in this novel.